Histopathological diversity of Rhinosinus Papillomas (Revista de Medicina Clinica, 2020)
BACKGROUND: Rhinosinus papillomas are benign epithelial neoplasms that originate from the respiratory epithelium. In 1991, the WHO of Health classified them into 3 histopathological subtypes: exophytic, inverted and oncocytic. Nasal papillomas, characterized by their ability to destroy, recurrence, predisposition for cell dysplasia and malignization.OBJECTIVE: To identify the main histolopathological varieties of rhinosinus papillomas in the ENT otolaryngology service, IMSS, Northwest.MATERIAL AND METHODS: A retrospective study was carried out, we reviewed the files from 2013 to 2018. We analyzed clinical and histological variables. We use X2 to evaluate the dichotomous categorical variables, the qualitative, nominal and ordinal variables, were interpreted by means of the calculation percentage, proportion, rate or relation. SPSS version 22.0 was usedRESULTS In the study period 68 patients were found, of which 38 met the criteria, the mean age 52.32 years, male gender were 22 (62%), the most frequent histopathological variety was inverted nasal papilloma 28 (80%), in the time of evolution of the disease â‰¥ 4 years were 22 (62%) the most common left side 19 (54%), the management was endoscopic in 28 (80%); in 11 (31%) they presented some degree of dysplasia , 9 (25.7%) presented recurrences. No relationship was found between recurrence and surgical technique P = 0.1013, if among those who presented some degree of dysplasia and recurrence P = 0.01747CONCLUSIONS The inverted nasal papilloma is the most frequent variety, the age in the fifth decade of life and recur more in those with some degree of dysplasia.
Keywords: rhinosinusal papilloma, histopathological diversity, dysplasia, comorbidity, recurrenc